2000
DOI: 10.1192/pb.24.9.327
|View full text |Cite
|
Sign up to set email alerts
|

Locked doors or sentinel nurses?

Abstract: Towards the end of 1998 we decided to introduce a facility to lock the doors of the acute psychiatric wards at Bootham Park Hospital, York. At first sight this would appear to be a retrograde step for modern psychiatric care in the UK. But this was a reasoned and planned move which has resulted in improved care for patients overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 3 publications
0
46
0
Order By: Relevance
“…How locked entrance doors at psychiatric wards are experienced by patients has been investigated in a very limited number of studies. A locked entrance door may be provocative (6), cause more worry, remind of a prison (2), and cause more anger and aggression (7) than experienced by patients at wards with open doors. Patients' satisfaction with treatment and care may be lower at a ward with a locked than an open door (8).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…How locked entrance doors at psychiatric wards are experienced by patients has been investigated in a very limited number of studies. A locked entrance door may be provocative (6), cause more worry, remind of a prison (2), and cause more anger and aggression (7) than experienced by patients at wards with open doors. Patients' satisfaction with treatment and care may be lower at a ward with a locked than an open door (8).…”
mentioning
confidence: 99%
“…It has been reported that some patients do not mind whether the door is locked or not (8). A locked door may signal safety, security and relief from real and imagined dangers (2,6,9). It has been reported that a locked entrance door may reduce the need for close observation, which patients may perceive as an advantage (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for locked units is the provision of greater safety for patients 14 15. Common risks in open wards include the availability of illicit drugs and absconding, the latter made more dangerous by environmental hazards that may be near the hospital, such as bridges, tall buildings and busy highways, all of which can compromise safety 2 14.…”
Section: Rationalementioning
confidence: 99%